2017
DOI: 10.1016/j.jmir.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Evaluating the Effectiveness of Dual-Registration Image-Guided Radiotherapy in Patients with Oropharyngeal Cancer

Abstract: The purpose of the article was to determine the impact of Dual Registration (DR) image-guided radiotherapy (IGRT) on clinical judgement and treatment delivery for patients with oropharyngeal cancer prior to implementation. METHODS Ninety Cone Beam Computed Tomography images from ten retrospective patients were matched using standard clipbox registration (SCR) and DR. Three image guided radiotherapy specialist radiographers performed all registrations and evaluated by; intra-class correlation to determine inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Fuss et al (5) reported that the translational error at the isocenter was 0.74 ± 0.53, 0.75 ± 0.60, and 0.93 ± 0.78 mm in the RL, CC, and AP directions, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuss et al (5) reported that the translational error at the isocenter was 0.74 ± 0.53, 0.75 ± 0.60, and 0.93 ± 0.78 mm in the RL, CC, and AP directions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is necessary to have high geometrical accuracy for a safe clinical application of precise radiotherapy. Some recent studies describe the process of measurement and reduction in geometrical errors [5][6][7]. There are some reviews which discuss different types of errors in radiotherapy and the process to overcome these discrepancies [3,[8][9][10].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…3-5 mm margins have been reported as appropriate only where daily IGRT [45,48], or alternating day IGRT [49,43] is routine practice. Where daily IGRT is not practiced studies recommended CTV-PTV margins of greater than 5 mm due to potential sub region set up variabilities in mandible, nasal septum and neck [50][51][52][53]24,54,55] and unstable set ups in patients with a high Body Mass Index (BMI) [50]. Random errors of up to 2-5 mm have been reported which could result in geometric miss if not imaged and corrected online where standard CTV-PTV margins are used [13,56,57].…”
Section: Ctv-ptv Margins Set Up Errors and Imaging Frequencymentioning
confidence: 99%
“…They reported that DR was an effective IGRT tool to ensure target coverage of inferior neck nodes as compared to SCR and have demonstrated acceptability to RT clinical practice. [11]…”
Section: Introductionmentioning
confidence: 99%